Integrated Marketing Communication and Its Effect on the revitalization of The Marketing Performance Field Research - حافظ, عبد الناصر علك; عبد الرزاق, محمد فاروق (Journal of Economics and Administrative Sciences, 2018)
The research topic was chosen because of the importance of communication in organizations in general and the marketing  process in particular. Without communication, the organization can not live and continue ,The problem of study diagnosis the reduction in sales in the company of plant oils in some its classes and weakness in differentiation and its reputation at market in spit if having good products with standardized features And lack of customer communication channels, also the company does not have any whole view about the concept of marketing communication, Therefore, This sudy aimed ro define to know the type of relationship between the extent of the impact of the integrated marketing communications an independent variable represented the nine dimensions and performance catalog dependent variable represented the four dimensions Using a descriptive and analytical approach That is formulated to search premises branched out of the nine major hypotheses, in order to achieve these objectives applied study the company of plant oils', in fact the size of sample is 84 person, and the researcher used analytic and descriptive method with using the statistical analysis program (spss-v23 ) with interviews, Statistical Methods showed a number of results, the most important active results with a good and positive relation between marketing communication and its dimensions with marketing performance. In conclusion, the researchers presented a set of recommendations and proposals, the most important The state should protect the products of company by application the customs taxes for imported products